Robert B. Parker's hot property [large type] - Parker, Robert B., 1932-2010; Lupica, Mike (Thorndike Press large print high octane., 2024)
"Spenser is waiting out the latest Boston snowstorm when he gets word that Rita Fiore has been shot. Both a pit bull in the courtroom and provocateur outside it, Rita is no stranger to controversy. But as one of the city's toughest lawyers, Spenser knows that there's no short list of suspects who might want to enact revenge. With Rita's life hanging in the balance, it's up to him to get to the bottom of things, even if it means unearthing some unsavory secrets that might just lead him into an age-old game of lies and deceit"--